Variations in food and feeding habits of Megalops cyprinoides fr coastal waters of Visakhapatnam - Rao, L M; Padmaja, G (Indian Journal of Fisheries, 2011)
The food and feeding habits of Megalops cyprinoides from the polluted waters of Visakhapatnam harbour in comparison with the unpolluted waters of Yerragedda. mouth have been investigated. There are marked differences in the food habits of the fish inhetween the two habitats. Prawns formed the main food item at the polluted Visakhapatnam -harbour-while aquatic insects dominated the gut contents at the unpolluted Yerragedda mouth. The reasons for the variation in food and feeding habits have been discussed in detail.